A new apterous species of the genus Orphnus MacLeay (Coleoptera: Scarabaeidae: Orphninae) from South Africa - Frolov, Andrey V. (Zootaxa, 2008)
The African continent has a diverse fauna of scarab beetles of the subfamily Orphninae with five genera and more than 100 described species (Arrow 1912, Frolov 2005).  The great majority of these species belong to the genus Orphnus MacLeay (Paulian 1948, Petrovitz 1971).  Most of the species in this genus have well-developed wings.  A few species, however, have reduced or almost absent wings.  Recently I had the opportunity to examine two apterous specimens from the Transvaal Museum, South Africa, belonging to an undescribed species similar to O. (Parorphnus) luminosus Benderitter.  This new species is described below.